Anthraquinone modification of microporous carbide derived carbon films for on-chip micro-supercapacitors applications. (20th August 2017) - Brousse, K.; Martin, C.; Brisse, A.L.; Lethien, C.; Simon, P.; Taberna, P.L.; Brousse, T.
Graphical abstract: Highlights: Carbide derived carbon (CDC) films were modified with anthraquinone (AQ) species. Electrochemical grafting of AQ was achieved in microporous carbon for the first time. 0.88 × 10 −10  mol cm −2 of AQ were grafted to 700 °C chlorinated on-chip CDC thin film. The total capacitance of the micro-supercapacitor electrodes was doubled in 1 M KOH. AQ grafting opens the way for an increase of CDC electrode capacitance Abstract: The modification of carbide derived carbon (CDC) thin film electrodes with anthraquinone (AQ) molecules was demonstrated by using pulsed chronoamperometry, in 0.1 M NEt4 BF4 /ACN solution of AQ diazonium derivative. The functionalization of CDC electrodes was only possible when a critical pore size is reached: only 2 nm pore diameter CDC can be grafted with AQ moieties, smaller pore size leading to a poorly functionalized electrode. High AQ surface coverage of 0.88 × 10 −10  mol.cm −2 was determined using 2 nm pore size CDC. Despite a decrease in double layer capacitance value of about 10%, the total capacitance of the AQ-modified on-chip CDC electrodes was twice larger than that of pristine CDC film, leading to high total capacitance value of 44 mF.cm −2 (338 F.cm −3 ). The cyclability of the AQ-modified on-chip CDC electrode was also investigated. The faradic contribution of AQ grafted molecules progressively decreased during cycling and only 39% of the normalized capacity remained after 500 cycles; this decrease has been assigned to electrostatic repulsion of dianionic AQ confined in narrow micropores in the alkaline media.